The crystal structure of tert-butyl (E)-3-(2-(benzylideneamino)phenyl)-1H-indole-1-carboxylate, C26H24N2O2 - Da Weihao; Kong Haonan; Wang Ruiyao; Lin Yi (Zeitschrift für Kristallographie - New Crystal Structures)
C26H24N2O2, monoclinic, P21/n (no. 14), a = 10.949(6) Å, b = 9.930(5) Å, c = 20.125(13) Å, β = 98.51(3)°, V = 2164(2) Å3, Z = 4, Rgt(F) = 0.0465, wRref(F2) = 0.1260, T = 296(2) K.